2000
DOI: 10.1111/j.1469-8749.2000.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year follow‐up of adolescent‐onset anorexia nervosa: physical health and neurodevelopment

Abstract: To study the development of physical health and some neuromotor functions in anorexia nervosa (AN) 51 individuals (48 females, three males) with a mean AN onset of 14 years, recruited after community screening, were followed prospectively together with 51 age-, sex-, and school-matched individuals without AN (controls). About 10 years after AN onset, all individuals were examined in respect of physical health and neurodevelopment. There were no deaths. Weight and height had normalised, except in three particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The set-shifting difficulties evident in this group of women with anorexia nervosa are largely consistent with previous reports from our group (2)(3)(4). Slowness on the dysdiadochokinesis test in anorexia nervosa, which did not reach statistical significance in our study, has also been reported by a different group (30,31). Our previous study using the same test battery (3) found no effects of SSRI medication use on neuropsychological performance.…”
Section: Discussionsupporting
confidence: 92%
“…The set-shifting difficulties evident in this group of women with anorexia nervosa are largely consistent with previous reports from our group (2)(3)(4). Slowness on the dysdiadochokinesis test in anorexia nervosa, which did not reach statistical significance in our study, has also been reported by a different group (30,31). Our previous study using the same test battery (3) found no effects of SSRI medication use on neuropsychological performance.…”
Section: Discussionsupporting
confidence: 92%
“…C. Gillberg, Gillberg, Rastam, & Johansson, 1996; Ivarsson, Rastam, Wentz, Gillberg, & Gillberg, 2000; Nilsson, Gillberg, Gillberg, & Rastam, 1999; Wentz, Gillberg, Gillberg, & Rastam, 2001). These researchers identified a cohort of 51 individuals with AN with a mean age of 16 years at baseline and now have followed this sample in parallel with an age-, sex-, and school-matched sample over a 10-year period (Nilsson et al, 1999; Wentz et al, 2001; Wentz, Gillberg, Gillberg, & Rastam, 2000). Baseline methodology included a semi-structured family-genetic interview with the child's mother regarding psychiatric, neurodevelopmental, and physical symptoms among first degree relatives, city-wide physical exams of all adolescent students, and blind medical chart reviews (I.…”
Section: The Extent Of Social Deficits In Anorexiamentioning
confidence: 99%
“…Results from this investigation supported a sustained pattern of interpersonal deficit in a subset of individuals with AN. Before discussing findings regarding social functioning, it is noteworthy that after 10 years only 39% of the sample with AN at baseline were free of eating disturbance compared with 90% of the comparison group (Wentz et al, 2000, 2001). Limiting our discussion to findings of interpersonal difficulties, individuals with ASD were overrepresented in the group with AN (28% vs. 12%), and of those individuals with AN who exhibited a poor outcome, individuals with ASD were disproportionately present (I.…”
Section: The Extent Of Social Deficits In Anorexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Perfectionism in childhood, a hallmark feature of OCPD, has also been identified as a risk factor for the development of AN and BN (Wade et al., 2016). Considerable research also demonstrates that the presence of OCPD traits is associated with poorer treatment response (Agras et al., 2014; Crane et al., 2007; Wentz et al., 2000). The culmination of this evidence has led to the hypothesis that OCPD traits may represent endophenotypic traits underpinning the development of AN and BN (Tenconi et al., 2010).…”
Section: Introductionmentioning
confidence: 99%